Value Creation Through Consolidation- Steel Sector - Nair, Vinod Sasidharan (2008)
The recent wave of mergers and consolidation in the steel sector and the trend to globalise the companies has given me the opportunity to study the effects of merger or acquisition activity on the share price and on the mean returns of the share price over a maximum window of one year. As mega deals are signed in this sector, the strategy behind these acquisitions are analysed in this study and recommendations are given for further consolidation and globalisation in the steel sector. The majority of the gains accumulate to the targets shareholders due to the premiums required by their shareholders in order to sell their shares. Hence, the returns to acquirers are historically shown to be neutral or even negative (Bild, 1998). However, some disparity in returns around the mean is expected, and as companies choose to continue to acquire, it is of interest to investigate this further. The general purpose of this dissertation is therefore to contribute with insight into how value is created through the merger or acquisition activity. Analysis is done on the share price and also the strategy implemented by these companies under scrutiny, as to find out whether the merger/ acquisition activity has created value. Share price has been analysed with the mean equality test, using the Eview software. Graph has been plotted for the time windows and the share price trend has been analysed over a maximum period of one year.